PROBLEMATIKA KETERAMPILAN MENULIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Subekti, Ani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explain the problems of Indonesian language in terms of writing skills in elementary school students. More specifically, the purpose of this study is to describe the writing skills of students, to find out the problems of writing skills in elementary schools, and solutions to improve writing skills. The method used in this research is descriptive qualitative with the type of case study.The subjects in this study were 28 fourth grade students and 1 homeroom teacher of SDN 1 Sendangrejo, Baturetno District, Wonogiri Regency. The instruments used in this study were observation, interviews, and student writing skills tests. The analysis techniques used were qualitative and quantitative. The results of the study showed that the writing skills of some students at SDN 1 Sendangrejo were still low. The results of the study showed that the problems of writing skills were influenced by several factors including lack of interest and motivation, limited vocabulary, spelling and punctuation problems, difficulty in structuring texts, minimal writing practice.